2005
DOI: 10.1097/01.fjc.0000184117.76188.68
|View full text |Cite
|
Sign up to set email alerts
|

Influence of CYP2D6 Genotype on Metoprolol Plasma Concentration and β-Adrenergic Inhibition During Long-Term Treatment

Abstract: In patients routinely treated with metoprolol, influences of CYP2D6 genotype on the response of heart rate to isoproterenol (IP) were studied at its peak and trough concentrations and were compared with those of bisoprolol. In 72 patients treated with metoprolol or bisoprolol, CYP2D6 genotype (ie, CYP2D6*1, *2, *4, *5, *10, and *14) was determined. No patients except one who was heterozygous for CYP2D6*5 carried the null alleles of CYP2D6. The homozygote frequency for CYP2D6*10 was relatively high (19.4%) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(39 citation statements)
references
References 22 publications
1
37
0
1
Order By: Relevance
“…The CL/F value in patients homozygous for the CYP2D6*10 allele was 64% lower than that in patients with the CYP2D6*1/*1 or *1/*2 genotype [12]. Nozawa et al showed, that in patients routinely treated with metoprolol, the CYP2D6 genotype significantly affects circadian variations of beta-adrenergic inhibition induced by metoprolol [13].…”
Section: Resultsmentioning
confidence: 99%
“…The CL/F value in patients homozygous for the CYP2D6*10 allele was 64% lower than that in patients with the CYP2D6*1/*1 or *1/*2 genotype [12]. Nozawa et al showed, that in patients routinely treated with metoprolol, the CYP2D6 genotype significantly affects circadian variations of beta-adrenergic inhibition induced by metoprolol [13].…”
Section: Resultsmentioning
confidence: 99%
“…14) In addition, isoproterenol-induced percentage increases in heart rate in Japanese patients with CYP2D6*10/*10, who were routinely treated with metoprolol, were less than those in the patients with CYP2D6*1/*1 or *1/*2. 34) These findings suggested that a lower dose of metoprolol may be used in the patients with CYP2D6*10. 14,34) In conjunction with the previous study, the present findings suggested that the pharmacokinetic variability of S-carvedilol is smaller than that of metoprolol (Fig.…”
Section: Discussionmentioning
confidence: 98%
“…34) These findings suggested that a lower dose of metoprolol may be used in the patients with CYP2D6*10. 14,34) In conjunction with the previous study, the present findings suggested that the pharmacokinetic variability of S-carvedilol is smaller than that of metoprolol (Fig. 4).…”
Section: Discussionmentioning
confidence: 98%
“…Есть данные, что бисопролол в отличие от метопролола оказывает относительно постоянный бета-блокирую-щий эффект вне зависимости от генотипа CYP2D6 [53], и в связи с этим может быть более предпочтителен у по-жилых, чем метопролол [13]. Кроме того, преимуществом бисопролола перед всеми другими β-адреноблокаторами является его двойной путь выведения, в связи с чем кор-рекция дозы требуется только при тяжелой степени по-чечной или печеночной недостаточности.…”
Section: Antiarrhythmic Drugs In Elderly Patients антиаритмические срunclassified